2016
DOI: 10.1007/s00453-015-0107-6
|View full text |Cite
|
Sign up to set email alerts
|

Deterministic Compression with Uncertain Priors

Abstract: We consider the task of compression of information when the source of the information and the destination do not agree on the prior, i.e., the distribution from which the information is being generated. This setting was considered previously by Kalai et al. (ICS 2011) who suggested that this was a natural model for human communication, and efficient schemes for compression here could give insights into the behavior of natural languages. Kalai et al. gave a compression scheme with nearly optimal performance, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(23 citation statements)
references
References 13 publications
0
23
0
Order By: Relevance
“…Third, we do not have any better lower bounds for the deterministic or imperfect-randomness settings, respectively from Haramaty and Sudan [4] and Canonne et al [10]. The known upper bounds in these settings are much weaker, featuring redundancy that grows at least linearly in the entropy of the source distribution, and in the case of the deterministic codes of Haramaty and Sudan, some kind of dependence on the size of the distribution's support.…”
Section: Suggestions For Future Workmentioning
confidence: 75%
See 2 more Smart Citations
“…Third, we do not have any better lower bounds for the deterministic or imperfect-randomness settings, respectively from Haramaty and Sudan [4] and Canonne et al [10]. The known upper bounds in these settings are much weaker, featuring redundancy that grows at least linearly in the entropy of the source distribution, and in the case of the deterministic codes of Haramaty and Sudan, some kind of dependence on the size of the distribution's support.…”
Section: Suggestions For Future Workmentioning
confidence: 75%
“…We briefly note that the definition of Haramaty and Sudan [4] differs in two basic ways. First, their definition does not include a common random string since they were primarily interested in deterministic coding schemes.…”
Section: The Model and Prior State Of The Artmentioning
confidence: 99%
See 1 more Smart Citation
“…The purpose in [5] of determining the chromatic number of the graphs described above was to solve the following compression problem: for some finite universe U, suppose that Alice is operating under the belief that a message m is chosen from U according to the probability distribution P , and that Bob operates under the belief that m is chosen according to the distribution Q. Both Alice and Bob know that their distributions P, Q are "close" in the sense that they know of some ∆ ≥ 0 such that max m∈U max log 2 P (m) Q(m) , log 2 Q(m) P (m) ≤ ∆.…”
Section: Motivationmentioning
confidence: 99%
“…Moreover, log * x denotes the minimum j such that log (j) x ≤ 1. Haramaty and Sudan [5] showed that for any k, s ∈ N the set of all chains of length 2k and size at most s can be colored with 2 6(s+1) · log (k) N colors so that for chains A, A ′ in this set with S 1 (A) ∩ S 1 (A ′ ) = ∅ and A 0 = A ′ 0 , A and A ′ receive different colors. As we will show in Section 3, this result is equivalent to the…”
Section: Introductionmentioning
confidence: 99%